Hydrodynamics and mass transfer in obstructed narrow channels - Feron, Paul H. M. (Cranfield University, 1991)
The objective of this research was to carry out a comprehensive investigation on hydrodynamics and mass transfer of different idealised geometries representing typical conditions which might occur in the narrow cells common in membrane process plant. The method used was to represent these cells by a ten times scale model, adjusting velocity and viscosity to match the Reynolds numbers which might occur in actual membrane equipment, typically between 100 and 1000. The geometries investigated had rods of circular cross-section placed at right angles to the direction of flow: the spacing, positioning and diameter of the rods were varied. Observations of flow patterns indicated that in most geometries flow instability arose at Reynolds numbers-of 200-300, i. e. an order of magnitude below the value at which it would arise in the empty channel. Pressure drop measurements showed that to a reasonable approximation the pressure loss per rod was constant for any given rod diameter. Flow instability did not significantly affect the rate of increase of pressure loss with increasing flow velocity. Mass transfer measurements and shear rate measurements using the diffusion limited current technique were made on these geometries. In contrast with pressure drop, mass transfer generally showed an upturn at higher values of the Reynolds number than the value at which flow instability set in. Local mass transfer and shear rate were correlated by means of a simple theoretical model. Excellent agreement was achieved for steady flow but agreement was only qualitative for unsteady flow. The conclusions which have emerged point the way to development of actual geometries superior, to those currently in use with respect to their pressure loss/mass transfer characteristics. These would improve the performance of membrane equipment, _and. possibly other mass and heat transfer processes in which geometry of this kind is encountered.